Study of optical reflectors for a 100ps coincidence time resolution TOF-PET detector design. (15th September 2021) - Gonzalez-Montoro, Andrea; Pourashraf, Shirin; Lee, Min Sun; Cates, Joshua W; Levin, Craig S
Abstract: Positron Emission Tomography (PET) reconstructed image signal-to-noise ratio (SNR) can be improved by including the 511 keV photon pair coincidence time-of-flight (TOF) information. The degree of SNR improvement from this TOF capability depends on the coincidence time resolution (CTR) of the PET system, which is essentially the variation in photon arrival time differences over all coincident photon pairs detected for a point positron source placed at the system center. The CTR is determined by several factors including the intrinsic properties of the scintillation crystals and photodetectors, crystal-to-photodetector coupling configurations, reflective materials, and the electronic readout configuration scheme. The goal of the present work is to build a novel TOF-PET system with 100 picoseconds (ps) CTR, which provides an additional factor of 1.5–2.0 improvement in reconstructed image SNR compared to state-of-the-art TOF-PET systems which achieve 225–400 ps CTR. A critical parameter to understand is the optical reflector's influence on scintillation light collection and transit time variations to the photodetector. To study the effects of the reflector covering the scintillation crystal element on CTR, we have tested the performance of four different reflector materials: Enhanced Specular Reflector (ESR) –coupled with air or optical grease to the scintillator; Teflon tape; BaSO4 paint alone or mixed with epoxy; and TiO2 paint. For the experimental set-up, we made use of 3 × 3 × 10 mm 3 fast-LGSO:Ce scintillation crystal elements coupled to an array of silicon photomultipliers (SiPMs) using a novel 'side-readout' configuration that has proven to have lower variations in scintillation light collection efficiency and transit time to the photodetector. Results : show CTR values of 102.0 ± 0.8, 100.2 ± 1.2, 97.3 ± 1.8 and 95.0 ± 1.0 ps full-width-half-maximum (FWHM) with non-calibrated energy resolutions of 10.2 ± 1.8, 9.9 ± 1.2, 7.9 ± 1.2, and 8.6 ± 1.7% FWHM for the Teflon, ESR (without grease), BaSO4 (without epoxy) and TiO2 paint treatments, respectively.